1994
DOI: 10.1037/0022-3514.66.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for universality and cultural variation of differential emotion response patterning.

Abstract: The major controversy concerning psychobiological universality of differential emotion patterning versus cultural relativity of emotional experience is briefly reviewed. Data from a series of cross-cultural questionnaire studies in 37 countries on 5 continents are reported and used to evaluate the respective claims of the proponents in the debate. Results show highly significant main effects and strong effect sizes for the response differences across 7 major emotions (joy, fear, anger, sadness, disgust, shame,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
496
1
15

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(549 citation statements)
references
References 47 publications
37
496
1
15
Order By: Relevance
“…Listeners can reliably recognize a broad range of vocally expressed emotions, even when the spoken words are unrelated to the emotion (Fairbanks and Pronovost, 1938;Belin et al, 2008;SimonThomas et al, 2009) or when recordings are filtered to remove segmental content (Lieberman and Michaels, 1962). Unlike the words that make up the segmental aspect of speech, affective vocalizations can be recognized across languages (Laukka et al, 2013), between cultures that have had only minimal historical contact (Sauter et al, 2010)-although with some cultural variation (Scherer and Wallbott, 1994)-and across species (Faragó et al, 2014). Indeed, infants who are hearing-impaired produce affective vocalizations that are acoustically similar to those of normal-hearing infants (Scheiner et al, 2004(Scheiner et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Listeners can reliably recognize a broad range of vocally expressed emotions, even when the spoken words are unrelated to the emotion (Fairbanks and Pronovost, 1938;Belin et al, 2008;SimonThomas et al, 2009) or when recordings are filtered to remove segmental content (Lieberman and Michaels, 1962). Unlike the words that make up the segmental aspect of speech, affective vocalizations can be recognized across languages (Laukka et al, 2013), between cultures that have had only minimal historical contact (Sauter et al, 2010)-although with some cultural variation (Scherer and Wallbott, 1994)-and across species (Faragó et al, 2014). Indeed, infants who are hearing-impaired produce affective vocalizations that are acoustically similar to those of normal-hearing infants (Scheiner et al, 2004(Scheiner et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different channels (or modes) of expression are likely to be involved in a single communicative act. The ability to discriminate audibly between vocal expressions of different categorical emotions has been found in different cultures and in some different languages (Scherer et al, 2001;Scherer & Wallbott, 1994). Investigating the auditory detection of facial expression is crucial not just for our understanding of perceptual processes but also because it could be vital for helping people with sensory deficits.…”
Section: Introductionmentioning
confidence: 99%
“…Then too, research into the conditions under which anger is aroused can also touch on the metatheoretical controversy as to whether emotions can be evoked independently of cognitions. Although we do not want to revive the now well-worn argument as to just what is involved in the concept cognition, if one adopts the relatively restricted definition favored by Izard (1993) and Zajonc 1 In their questionnaire study of some 2,900 university students on five continents, Scherer and Wallbott (1994) found that, for the emotions they investigated, the similarities in reported emotion-specific feelings, physiological symptoms, and bodily expressions across countries were much greater than the variations among the countries. And they concluded that "The data reported here do not support an extreme position of cultural relativism with respect to emotional experience" (p. 324).…”
mentioning
confidence: 96%
“…E-mail: lberkowi@wisc.edu 1 In their questionnaire study of some 2,900 university students on five continents, Scherer and Wallbott (1994) found that, for the emotions they investigated, the similarities in reported emotion-specific feelings, physiological symptoms, and bodily expressions across countries were much greater than the variations among the countries. And they concluded that "The data reported here do not support an extreme position of cultural relativism with respect to emotional experience" (p. 324).…”
mentioning
confidence: 99%